Springer handbook of advanced catalyst characterization - Bañares, Miguel A.; Wachs, Israel E. (Springer Handbooks,, 2023)
Co-edited by world-renowned scientists in the field of catalysis, this book contains the cutting-edge in situ and operando spectroscopy characterization techniques operating under reaction conditions to determine a materials bulk, surface, and solution complex and their applications in the field of catalysis with emphasis on solid catalysts in powder form since such catalyst are relevant for industrial applications. The handbook covers from widely-used to cutting-edge techniques. The handbook is written for a broad audience of students and professionals who want to pursue the full capabilities available by the current state-of-the-art in characterization to fully understand how their catalysts really operate and guide the rational design of advanced catalysts. Individuals involved in catalysis research will be interested in this handbook because it contains a catalogue of cutting-edge methods employed in characterization of catalysts. These techniques find wide use in applications such as petroleum refining, chemical manufacture, natural gas conversion, pollution control, transportation, power generation, pharmaceuticals and food processing.